The Influence of Religious Beliefs and Social Stratification Upon Bangka-Bangka Burial Sites in Mamasa Districk - Rosmawati (Hasanuddin University, 2021)
Bangka-Bangka burial sites were commonly practiced in Mamasa in the past, but now, this cultural tradition is in danger of extinction. The Bangka-Bangka grave remains are also almost going extinct. Despite this, it is important to investigate to which extent religious beliefs and social stratification exert influence upon the Bangka-Bangka Burial Sites seen from grave styles of Bangka Bangka in Mamasa, Eastern Indonesia. This study aims to investigate factors which influences Bangka-Bangka Burial Sites in Mamasa. An archaeological survey (field survey) along with an interview with local community members was used to collect data. As the result, Bangka-Bangka Burial Sites in Mamasa were much influenced by cosmological beliefs shaped by rules of Aluk To Dolo and royal family stratification.